Mad-maximized Higgs pair analyses - Kling, Felix; Plehn, Tilman; Schichtel, Peter (Arxiv, 2016)
We study Higgs pair production with a subsequent decay to a pair of photons and a pair of bottoms at the LHC. We use the log-likelihood ratio to identify the kinematic regions which either allow us to separate the di-Higgs signal from backgrounds or to determine the Higgs self-coupling. We find that both regions are separate enough to ensure that details of the background modelling will not affect the determination of the self-coupling. Assuming dominant statistical uncertainties we determine the best precision with which the Higgs self- coupling can be probed in this channel. We finally comment on the same questions at a future 100 TeV collider.